A 250‐Year, Decadally Resolved, Radiocarbon Time History in the Gulf of Maine Reveals a Hydrographic Regime Shift at the End of the Little Ice Age. Issue 9 (23rd September 2020) - Lower‐Spies, Erin E.; Whitney, Nina M.; Wanamaker, Alan D.; Griffin, Shelly M.; Introne, Douglas S.; Kreutz, Karl J.
Abstract: In order to document relative changes in water mass contributions in the Gulf of Maine (GoM), we used the shell material of the long‐lived ocean quahog ( Arctica islandica ). A multicentury, crossdated master shell growth chronology facilitated the reconstruction of a radiocarbon Δ 14 C history prior to the radiocarbon bomb‐pulse of the 1950s. This reconstruction reveals a highly variable Δ 14 C series (mean = −56.6 ± 8.0‰ (1σ); N = 34) from CE 1685 to 1935. Δ 14 C values indicate a rapid shift ca. 1860 CE in source waters to the GoM. From CE 1685 to 1860, GoM waters were dominated by an admixture of Warm Slope Water primarily composed of tropical Atlantic surface waters/Gulf Stream Waters, and Scotian Shelf Water. This water regime was followed by a rapid Δ 14 C transition to a Labrador Slope Water endmember after CE 1860, with an apparent decrease in Scotian Shelf Water. Together, this shift is likely related to broader changes in the Arctic and the Labrador Sea, and a short‐term strengthening of the Atlantic meridional overturning circulation. Labrador Slope Water dominating GoM hydrography in the 1900s is verified by the similarities between this record and other coral‐ and shell‐derived Δ 14 C records influenced by waters with Labrador Sea origin. This suggests that GoM radiocarbon variability broadly reflects large‐scale ocean circulation processes in the Northwestern Atlantic. The lack of Δ 14 C values much below the Labrador Slope Water endmember suggests that the interior GoM gets very little to no Antarctic Intermediate Water as other studies had previously suggested. Plain Language Summary: The Gulf of Maine (GoM), a region of the North Atlantic along the east coast of the United States, is both an ecologically and economically important system that is rapidly changing with climate change. Understanding how the environmental conditions in the GoM have changed in the past will help predictions of what will happen in the future in this region. This study investigates changes in ocean conditions, specifically the different types of water coming into the GoM, over the last 300 years. Waters flowing into the GoM have different physical properties, including temperature, salinity, and nutrient concentrations depending on their origin. These waters vary in their chemical properties as well, including radiocarbon content. The radiocarbon chemical signature in the water is captured in clam shells during their lifetime. Our results indicate that the radiocarbon signature stored in the clams rapidly changes around CE 1860 indicating a shift in source waters flowing into the GoM. We also show that waters in the GoM have very similar radiocarbon chemical signatures to those measured outside of the GoM through time. This result confirms that the composition of waters in the GoM is strongly influenced by waters in the broader North Atlantic region. Changes in North Atlantic circulation both north and south of the GoM likely caused the rapid change seen in the radiocarbon record around 1860. Key Points: The water masses feeding the Gulf of Maine have different radiocarbon signatures related to ventilation and upwelling processes Radiocarbon measured in absolutely dated Arctica islandica shells is used to track water masses entering the Gulf of Maine over 250 years Radiocarbon time series reveal an abrupt regime shift around CE 1860 as a result of oceanographic changes in the North Atlantic